The Effect of Geographic Expansion Strategy and Fintech Integration on Operational Efficiency and Business Scalability of On-Demand Service Platform Companies (A Study of Gojek and Grab in Indonesia) - Dwi Winahyo Sutrisna (Return : Study of Management, Economic and Bussines, 2026)
Background: The rapid growth of on-demand service platforms in Indonesia, particularly Gojek and Grab, has transformed the digital economy landscape. However, the strategic mechanisms through which geographic expansion and fintech integration jointly influence operational efficiency and business scalability remain underexplored. Objective: This study analyzes the impact of geographic expansion strategies and fintech integration on the operational efficiency and business scalability of on-demand service platform companies in Indonesia, focusing on Gojek and Grab. Methods: The research employs a systematic literature review approach, synthesizing findings from academic journals, industry reports, and official documents. The analysis integrates literature on geographic expansion, two-sided platforms, fintech ecosystems, and digital business scalability. Results: The findings reveal that rapid expansion supported by disruptive technology has enabled both platforms to enter new markets, strengthen their economic contribution, and transform consumer behavior. Fintech integration through services such as GO-PAY, OVO, and GrabPay significantly improves operational efficiency through accelerated transactions, expanded financial access, and digital process automation. Furthermore, the development of digital ecosystems and innovative collaboration between fintech providers and digital banks enhances business scalability and sustainability. Conclusion: This study concludes that strategic geographic expansion and fintech integration are mutually reinforcing drivers of platform competitiveness. The findings underscore the importance of ecosystem development and digital infrastructure in supporting the growth of the on-demand services industry in Indonesia. The research contributes theoretically to digital platform literature and offers practical implications for platform managers and policymakers.